EMPLOYMENT ISSUES OF LABOR RESOURCES IN THE REPUBLIC OF ARMENIA - Manucharyan Meri Gagiki (International Journal of Innovative Technologies in Economy, 2018)
Employment relations, being one of the most important aspects of public life, are in the limelight of legislators. It should be noted that the decline in the number of labor resources is observed year by year, for example, in 2016, compared to 2015, labor resources have dropped by 95.2 thousand people. The global experience of employment in the state of employment shows that there is no single prescription for employment in all countries. It is different in different countries, depending on the degree of economic and social development of the given country and its national peculiarities. Observing the economic policy of our state in the sphere of employment, one can conclude that it has a passive nature and cannot make substantial positive changes in the labor market.